Issues in International Exchange and Payments Systems - Quirk, Peter (Washington, D.C. : International Monetary Fund, 1995)
The global trend toward lilberalization in countries international payments and transfer systems has been widespread in both industrial and developing countries and most dramatic in Central and Eastern Europe. Countries in general have brought their exchange systems more in line with market principles and moved toward more flexible exchange rate arrangements. This study updates previous studies published under the title Developments in International Exchange and Payments Systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet